Investigating Arabic Foreign Learning In Indonesian Context: It’s Necessety Or The Demand? - M. Abdul Hamid; Rizka Widayanti; Suci Ramadhanti Febriani; Ayu Desrani; Yasmadi Yasmadi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study aims to investigate student perceptions of learning Arabic from the aspect of learning objectives and strategies for improving the Arabic language skills. This study uses a mixed approach with survey methods and qualitative design with data analysis techniques based on triangulation of data sources. The results show that the orientation of Arabic learners aims to study religion from the Qur'an and Sunnah as well as communication orientation, while the learning strategies they choose vary widely; improving listening skills through watching movies, listening to songs and lectures; speaking skills strategies include communicating collaboratively and practicing independently; reading skills strategies include reviewing readings, reading short stories, and Arabic news; writing skills strategies include writing intensive (imla’), answering questions. The findings reveal that, the first is integration of student achievements to master Arabic is a global need, where Arabic is a forum for international communication and the second is electric method can accelerate students' Arabic skills. This research is still limited to variables and discussion topics, so it recommends further research to measure the effectiveness of each strategy adopted by Arabic learners in Indonesia.